Digitalization of Learning Media through Digital Book Development Using the Flipbook Application - Meylani Astino Perdana; Dodiet Enggar Wibowo; Mochamad Kamil Budiarto (Jurnal Pendidikan dan Pengajaran, 2021)
The development and advancement of information and communication technology that penetrates various fields of human life had enormous potential to be used, therefore it was important to integrate thoroughly between technology into the learning process. This study aims to develop a flipbook-based digital as an instructional media that was suitable for the learning activities. This research approach was research and development (RnD) with the ADDIE as a development model which consists of Analysis, Design, Development, Implementation, Evaluation. However, this research only focuses on knowing the feasibility level of the flipbook. The subjects of this study were media experts (2 people), material experts (2 people), subject teachers (4 people), and 44 high school class XI Science students. The research instrument used a Likert scale of 1 - 5 to find out the opinions of each validator of the flipbook as instructional media. The results of assessment from each validator will be analyzed descriptively using a percentage to determine the level of feasibility. The results showed that the flipbook-based digital media was included in the category of "feasible" to be used as an instructional learning media for biology class in high school, this was indicated by the results of the validation by each of the validators who obtained a “feasible” result.